Efektifitas Qigong Exercise Selama Kehamilan dalam Pencegahan Gejala Depresi Post Partum pada Ibu Remaja - Puspasari, Jehan; Fanani, Dian FItria (Jurnal Kesehatan Holistic, 2020)
One problem encountered in a woman after giving birth is postparum depression. This problem must be addressed through nursing interventions in improving the health of mothers and babies, one of the interventions is qigong exercise. The objective of this research was to identify qigong exercise’s effectiveness during pregnancy to preventing adolescent mother’s postpartum depression. This quasi experiment study applied a purposive sampling technique. The samples were 27 adolescent mothers. The instruments were structured questionnaires, including demographic questionnaire and Edinburgh Postnatal Depression Scale (EPDS). The variable of postpartum depression including pre-intervention and post-intervention were analyzed using Wilcoxon test. The results showed that there was a effectiveness between qigong exercises and postpartum depression’s prevention of adolescent mothers with p value of 0.000. Physically and mentally well-being of adolescent mothers’ greatly affects to performing nurturing.